Anxiety and Motivation in the Acquisition of Speaking Ability - Khudriyah Khudriyah; Julianne Kamilia Riza; Mamik Rosita; Ali Mustofa (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This research aims to determine whether or not anxiety influences motivation, whether anxiety affects speaking skills, whether motivation influences speaking ability, and whether motivation significantly mediates the influence of anxiety on speaking ability. The research approach is quantitative; the sample of this study comprised 137 students from two schools: 99 respondents from MA al Urwatul Wutsqo and 38 from MA Arrahman Jombang. The sample was determined through stratified random and saturation sampling. The data were collected through a questionnaire and documentation of students' speaking scores, and analyzed using Structural Equation Modeling with AMOS 22. Validity, reliability, normality, and Goodness of Fit were used to assess the feasibility and interpretability of the hypothesis test. The result of the hypothesis was that there is a negative effect of anxiety on students’ motivation, there is a negative effect of anxiety on students’ speaking ability, there is a positive effect of students’ motivation towards students’ speaking ability, and motivation can mediate the influence of anxiety towards speaking ability of students at MA al Urwatul Wutsqo and MA Arrahman Jombang.